Enhanced tensile ductility of an additively manufactured AlSi10Mg alloy by reducing the density of melt pool boundaries. (December 2022) - Chen, Haoxiu; Patel, Sagar; Vlasea, Mihaela; Zou, Yu
Abstract: AlSi10Mg components produced by laser powder bed fusion (LPBF) typically exhibit higher strength but lower ductility than those made by conventional mature processing technologies. The effects of melt pool boundaries on the ductility and fracture behavior of the LPBF-produced AlSi10Mg have not been systematically studied. The focus of this work is to investigate the local strain evolution, microvoid growth, and crack formation in the melt pool boundary regions using in situ tensile testing and synchrotron-based X-ray microtomography. Results indicate that decreasing area fractions of melt pool boundaries from 5.48% to 4.48% leads to an increase of tensile ductility from 7.2% to 9.8% in the LPBF AlSi10Mg samples. By influencing the density of melt pool boundaries in the LPBF process, while maintaining part density, we offer a new opportunity to fabricate AlSi10Mg products with an excellent combination of high strength and ductility. Graphical abstract: Image, graphical abstract